Understanding microwave treatment of ores - Jones, Dafydd Aled (2005)
Microwave energy has previously been shown to have a major influence on the comminution behaviour of minerals and ores. Significant reductions in strength have been observed for microwave-treated ores. Other workers have reported increases in liberation after treatment. However, the majority of the work has been carried out at energy inputs too high for economic implementation. Whilst it was thought that the weakening and enhanced liberation was due to differential expansion of the heated constituent phases resulting in increased predominance of inter-granular fracture, the exact mechanisms have been poorly understood. Due to difficulties in measuring events inside a microwave cavity and inside the material being irradiated, it was suggested that numerical modelling could be used to simulate a simplified system in order to determine the underlying mechanisms. The model was used to examine the development of stresses as heat was applied to certain mineral phases. No heat was applied directly to the matrix component of the simulated ore. Given sufficient energy input, the stresses would exceed the strength of the material. It was found that the shear stresses in particular were likely to be highest at the edges of the grain boundaries of 2-D circular heated particles inside an unheated (microwave-transparent) matrix. This explained the increased occurrence of inter-granular fracture which has led to observations of enhanced liberation. It was also discovered that weakening is facilitated at very high microwave power densities, due to the increased magnitude of expansion and subsequent forces generated. The overall energy balance can be made favourable by using microwave exposure times of less than 0.1 seconds. Shorter exposure times result in less time for conduction to occur from the heated phase into the unheated phase, and temperature gradients are maximised leading to elevated shear stresses and increased likelihood of fracture.